Habitat restoration and faunal recovery: A review (Zoological Records and Reviews, 2025)
Habitat restoration -- the deliberate intervention to assist recovery of a degraded or destroyed ecosystem toward areference condition -- has emerged as a central strategy for biodiversity conservation and is now mandated at scalethrough the EU Nature Restoration Law (2024/1991) and the Kunming-Montreal Global Biodiversity Framework 30x30and restoration targets. This review synthesises evidence from 284 peer-reviewed studies published between 2000 and2024 on faunal recovery following habitat restoration across European terrestrial and freshwater ecosystems, coveringsix restoration types (riparian, peatland, heathland, grassland, woodland, and river floodplain) and five vertebrate andinvertebrate groups. Meta-analysis of 148 studies providing quantitative recovery data confirms that restoration increasesfaunal diversity by a mean of 34.8% (95% CI: 28.4-41.2%) relative to degraded controls, but recovery to referencecondition levels takes 8-42 years depending on taxon and restoration type. Recovery rates are highest for mobilegeneralists (breeding birds, butterflies; mean 85.4% of reference richness at 10 years) and slowest for sedentaryspecialists (freshwater molluscs, amphibians; mean 42.4% at 10 years). The single most important predictor ofrestoration success across all studies was donor-population connectivity -- access to source populations forrecolonisation -- which accounted for 38.4% of variance in recovery rate (partial R2 in meta-regression). Managementintensity post-restoration (active vegetation management, predator control, water level management) was the secondmost important predictor (partial R2 = 0.24). These findings provide an evidence synthesis for prioritising restorationinvestment and design under EU Nature Restoration Law national planning obligations.